Pelatihan Edukator Sebaya Mengenai Pernikahan Dini pada Remaja di Kabupaten Bandung Barat: Peer Educator Training on Early Marriage for Teenagers in West Bandung Regency - Prawiradilaga, Rizky Suganda; Makaginsar, Caecielia; Indrasari, Eva Rianti; Yuniarti, Yuniarti; Yulianti, Arief Budi; Putri, Mirasari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In developing countries such as Indonesia, early marriage is still common, resulting in various negative impacts. This community service aims to provide high school students in West Bandung Regency (KBB) with an understanding of the importance of reproductive health to prepare them for marriage. This community service activity involves training peer educators on reproductive health to reduce the rate of early marriage. Conducted in June 2023 at SMA Madrasah Aliyah swasta (MAs) Persis in Padalarang, KBB, the session was aimed at 35 eleventh grade students. The methodology consisted of five stages: The first stage was administrative preparation and coordination; The second stage was implementation, starting with a pretest, then education on reproductive organs, pregnancy process, early marriage, reproductive health, sexually transmitted infections, and reproductive organ care, followed by discussion and post-test; The third stage involved improving students' public speaking skills; The fourth stage was mentoring the students in the form of providing a pocket book on reproductive health as a practical guide; The fifth stage was evaluation. The community service activities successfully improved participants' knowledge on reproductive health, encouraging better self-care practices and preventive measures. Through the peer educator training, students at MAs Persis Padalarang gained effective communication skills to disseminate reproductive health information among peers, thus increasing awareness and understanding within their community.